Response to anti-HBV vaccine and 10-year follow-up of antibody levels in healthcare workers. (October 2016) - La Fauci, V.; Riso, R.; Facciolà, A.; Ceccio, C.; Lo Giudice, D.; Calimeri, S.; Squeri, R.
Abstract: Background: Despite improvements in public health and antiviral treatments, vaccination is still the most effective means of prevention of hepatitis B virus (HBV) infection. However, little is known about the duration of protection given by the anti-HBV vaccine. Healthcare workers represent a category at risk not only of contracting infection but also of being a source of contagion to patients. Objectives: To assess individual responses to the anti-HBV vaccine and duration of protection 10 years after its administration in a cohort of healthcare workers employed by the University Hospital 'G. Martino' in Messina, Italy. Methods: One hundred and seventy medical staff who had been vaccinated following an incident carrying risk of HBV infection were included in this study. The group was followed over a 10-year period, and HBV antibody levels were assessed using an automated microparticle enzyme immunoassay. Results: Protective antibody levels (≥10 mIU/ml) were found in 65% of subjects who had completed the full vaccine schedule (three doses) and in 35% of subjects who had only received one or two doses of anti-HBV vaccine. Moreover, 10 years after vaccination, HBV antibody levels were inversely related to age at vaccination ( P < 0.001). No differences were found between males and females. Conclusions: This study, in line with the literature, shows the importance of completing the full vaccine schedule (three doses). Moreover, in order to have an effective and durable antibody response and avoid the risk of contracting HBV after an injury at work, it is important to recommend anti-HBV vaccination at a young age, ideally during childhood in accordance with the national vaccination policy. Highlights: Vaccination is still the most effective means of preventing HBV infection. Healthcare workers (HCWs) represent a category at risk for HBV infection. It is unclear the duration of antibody coverage after the hepatitis B vaccination. We investigated the response to vaccine and duration of protection for ten years. Our study underlines the importance of completing the entire vaccine schedule.